Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
Para determinar [tex]\( a^2 + b^2 + 3a + 3b \)[/tex] dados los valores [tex]\( a + b = 0 \)[/tex] y [tex]\( ab = 3 \)[/tex], sigamos los siguientes pasos detalladamente:
1. Comencemos con las ecuaciones dadas:
- [tex]\( a + b = 0 \)[/tex]
- [tex]\( ab = 3 \)[/tex]
2. Calculemos [tex]\( a^2 + b^2 \)[/tex] utilizando una identidad algebraica:
- Sabemos que:
[tex]\[ (a + b)^2 = a^2 + b^2 + 2ab \][/tex]
- Dado que [tex]\( a + b = 0 \)[/tex], podemos sustituir en la identidad:
[tex]\[ (0)^2 = a^2 + b^2 + 2ab \][/tex]
- Esto se simplifica a:
[tex]\[ 0 = a^2 + b^2 + 2ab \][/tex]
3. Sustituir el valor de [tex]\( ab \)[/tex] en la ecuación anterior:
- Dado que [tex]\( ab = 3 \)[/tex]:
[tex]\[ 0 = a^2 + b^2 + 2(3) \][/tex]
- Esto se simplifica a:
[tex]\[ 0 = a^2 + b^2 + 6 \][/tex]
- Resolviendo para [tex]\( a^2 + b^2 \)[/tex], obtenemos:
[tex]\[ a^2 + b^2 = -6 \][/tex]
4. Calculemos el término [tex]\( 3a + 3b \)[/tex]:
- Dado que [tex]\( a + b = 0 \)[/tex], multiplicamos ambos lados por 3:
[tex]\[ 3a + 3b = 3 \times 0 = 0 \][/tex]
5. Sumemos los resultados obtenidos:
- Tenemos que [tex]\( a^2 + b^2 = -6 \)[/tex] y [tex]\( 3a + 3b = 0 \)[/tex].
- Entonces:
[tex]\[ a^2 + b^2 + 3a + 3b = -6 + 0 = -6 \][/tex]
Por tanto, el valor de [tex]\( a^2 + b^2 + 3a + 3b \)[/tex] es [tex]\(\boxed{-6}\)[/tex].
1. Comencemos con las ecuaciones dadas:
- [tex]\( a + b = 0 \)[/tex]
- [tex]\( ab = 3 \)[/tex]
2. Calculemos [tex]\( a^2 + b^2 \)[/tex] utilizando una identidad algebraica:
- Sabemos que:
[tex]\[ (a + b)^2 = a^2 + b^2 + 2ab \][/tex]
- Dado que [tex]\( a + b = 0 \)[/tex], podemos sustituir en la identidad:
[tex]\[ (0)^2 = a^2 + b^2 + 2ab \][/tex]
- Esto se simplifica a:
[tex]\[ 0 = a^2 + b^2 + 2ab \][/tex]
3. Sustituir el valor de [tex]\( ab \)[/tex] en la ecuación anterior:
- Dado que [tex]\( ab = 3 \)[/tex]:
[tex]\[ 0 = a^2 + b^2 + 2(3) \][/tex]
- Esto se simplifica a:
[tex]\[ 0 = a^2 + b^2 + 6 \][/tex]
- Resolviendo para [tex]\( a^2 + b^2 \)[/tex], obtenemos:
[tex]\[ a^2 + b^2 = -6 \][/tex]
4. Calculemos el término [tex]\( 3a + 3b \)[/tex]:
- Dado que [tex]\( a + b = 0 \)[/tex], multiplicamos ambos lados por 3:
[tex]\[ 3a + 3b = 3 \times 0 = 0 \][/tex]
5. Sumemos los resultados obtenidos:
- Tenemos que [tex]\( a^2 + b^2 = -6 \)[/tex] y [tex]\( 3a + 3b = 0 \)[/tex].
- Entonces:
[tex]\[ a^2 + b^2 + 3a + 3b = -6 + 0 = -6 \][/tex]
Por tanto, el valor de [tex]\( a^2 + b^2 + 3a + 3b \)[/tex] es [tex]\(\boxed{-6}\)[/tex].
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.